Measurement of luteinizing hormone surge in vaginal discharge: a potential biomarker that enables simple, non-invasive prediction of the periovulatory period - Moto Takeshita; Keita Saito; Yuya Suzuki; Wataru Yoshimasa; Risako Hayashi; Yoko Chiba (BMC, 2024)
Abstract Background Predicting the periovulatory period is very important for conception. Current approaches to predicting the periovulatory period include monitoring of basal body temperature and urine luteinizing hormone (LH) concentration; however, these methods are time-consuming. Here, we examined the potential of using vaginal discharge (VD) as a non-invasive means of sample collection for determining the LH surge that indicates ovulation. Methods Urine and VD samples were collected from 35 healthy women aged 20-39 years. VD samples were collected with panty liners to reduce the burden on participants. Daily first urine samples and used panty liners were collected from the 10th through 19th days of the menstrual cycle. Urine and VD LH (uLH and vLH) levels in the samples were measured by enzyme-linked immunosorbent assay. Measured vLH baseline and first surge values were analyzed using Student's t-test and ROC curves. Results Samples for a total of 55 menstrual cycles were collected. We used uLH surge to establish the date of ovulation. uLH surges were observed in 49 cycles, 34 of which had corresponding VD samples that qualified for measurement. Five cycles were excluded due to a lack of vLH data. In the remaining 29 cycles, the vLH surge appeared within the fertile window 90% of the time, and the sensitivity and specificity of the test were 86% and 83%, respectively. Conclusions VD has potential for use as a sample for predicting the periovulatory period by measuring LH content.